Strategi Guru Dalam Mengatasi Perilaku Agresif Anak Usia Dini di TK Negeri Kihadjar Dewantoro 1 - Karim, Ainun; Utoyo, Setiyo; Laiya, Sri Wahyuningsi (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2024)
This study aims to determine the teacher's strategy in dealing with aggressive behavior in early childhood at Kihadjar Dewantoro 1 State Kindergarten, Kota Timur District, Gorontalo City. The method used in this research is descriptive qualitative with observation data collection techniques, interviews, and documentation. Based on the results of the research discussion, the strategy for dealing with early childhood aggressive behavior applied by teachers in Kihajdar Dewantoro 1 State Kindergarten, Kota Timur District, Gorontalo City, has been able to handle and minimize the occurrence of aggressive behavior. The results of this study describe the teacher's strategy for dealing with early childhood aggressive behavior in Kihajdar Dewantoro 1 State Kindergarten, Kota Timur District, Gorontalo City, that the strategy applied by the teacher has undergone changes for the better. Such as identifying children's problems by looking at and recording children's behavior with anecdotal notes. Then a gentle approach strategy by giving persuasion and giving praise. However, if a gentle approach strategy is not effective, a punishment strategy will be used.